Las actividades lúdicas en el proceso de adaptación en los niños de 4 a 5 años en la unidad educativa “Fernando Daquilema” del cantón Riobamba, provincia de Chimborazo, período 2015-2016 - Chisaguano Aynaguano, Paola Alexandra; Moyano Ocaña Leonela Liseth (2016)
The research titled “Playful activities in the adaptation process in children 4-5 years old in Unidad Educativa “Fernando Daquilema” of Riobamba canton, Chimborazo province, period 2015-2016. It was carried out with the purpose of offering a contribution to the difficulties that occur in the early days of classes in the preschool age children, because as, it is relevant knowledge to impart teaching-learning tactics to children at an early age allowing intellectual development is much more important to their development. Therefore, every child needs an adaptation phase to new environment, and then it is better to implement to students valid playful activities for achieving this objective. In the research work were involved 64 students, who were distributed 30 girls and 34 boys attending initial education, the purpose is to achieve their adaptation to their learning environment. The research is descriptive-explanatory for describing and providing the necessary explanations of why the boys and girls are learning or not. This was accompanied with the theoretical framework related at two variables of study playful activities and the adaptation process. Techniques and instruments and observation sheet were applied, it was an important part for knowing how valuable the research contribution is to the institution. It has also planned a variety of playful activities for students to interact with each other and therefore they have a better development in their teaching process, deductive, inductive, analytic, and synthetic methods were applied, it was an essential contribution to decision-making in research. Finally, the conclusions and recommendations were addressed to the staff that is part of the Unidad Educactiva Fernando Daquilema.